Answer:
Due to the resistance of air, a drag force acts on a falling body (parachute) to slow down its motion. Without air resistance, or drag, objects would continue to increase speed until they hit the ground. The larger the object, the greater its air resistance. Parachutes use a large canopy to increase air resistance. Also, Once the parachute is opened, the air resistance overwhelms the downward force of gravity. The net force and the acceleration on the falling skydiver is upward. An upward net force on a downward falling object would cause that object to slow down. The skydiver thus slows down. Sorry if not helpful.
Answer:
12.5 m/s
Explanation:
From the question given above, the following data were obtained:
Initial velocity (u) = 0 m/s
Height (h) = 8 m
Final velocity (v) at 8 m above the lowest point =?
NOTE: Acceleration due to gravity (g) = 9.8 m/s²
The velocity of the roller coaster at 8 m above the lowest point can be obtained as follow:
v² = u² + 2gh
v² = 0² + (2 × 9.8 × 8)
v² = 0 + 156.8
v² = 156.8
Take the square root of both side
v = √156.8
v = 12.5 m/s
Therefore, the velocity of the roller coaster at 8 m above the lowest point is 12.5 m/s.
The answer to this is Helium :) it's in the farthest right columb and is a noble gas.
please mark as brainliest!
Answer:
9 and 3 N
Explanation:
Forces in the same direction sum up to produce the resultant force;
One force subtract the other will give the resultant force when they are in opposite directions;
Lets say one direction is forwards and the opposite backwards;
We have one force, let's say force A, in the forwards direction and another force, force B, acting in the same (forwards) or opposite (backwards) direction;
If B is acting in the same direction, then the resultant force (in this case) will be as follows:
A + B = 12
If B is acting in the opposite direction, then the resultant force will be as follows:
A - B = 6
Summing the two equations will allow us to solve for A:
A + B + (A - B) = 12 + 6
2A = 18
A = 9
Substitute this into either of the above equations and we can solve for B:
(9) - B = 6
B = 9 - 6
B = 3